Business Model of Jamu as Indonesian Traditional Herbal Medicine in New Economy - Amalia, Fatya Alty; Aprianingsih, Atik (The Asian Journal of Technology Management (AJTM), 2017)
Abstract. Many firms in New Economy tend to depend more on intangible resources (i.e. knowledge and information) than tangible resources as in Old Economy. This shifting has made many firms favour the information technology for their daily business conducts today. The fast spreading of information leads to the fiercer competition than before. The great recognition of intangible assets somewhat calls for the notion of a new business model. Some enterprises and researchers expect this effort may generate more value for today’s competition through combining all assets in proper judgments. Jamu, Indonesian traditional herbal medicine, also cannot avoid the impact of New Economy competition. Jamu enterprises need to preserve the traditional value in the midst of the modern lifestyle. Then, the urgency to maintain Jamu competitive advantage is felt necessary. To provide the new business model of Jamu that is deemed as appropriate in New Economy’s competition is the aim of this study. Through analysing various literature, the authors heavily consider Product Service System (PSS), specifically the product-oriented type to construct a new business model for Jamu.Keyword: Jamu, new economy, PSS, product-oriented, business model